DETERMINAN NPL BANK UMUM DI INDONESIA ERA PANDEMI COVID-19 - Tandiari, Salsabila Putri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
During the Covid-19 pandemic, the NPL level for commercial banks in Indonesia has shown an increasing trend for two years. This indicates that defaults by debtors during the Covid-19 pandemic are increasing considering The number of individuals who have experienced job loss and the decreased income earned by companies. Therefore, the objective of this study is to examine the impact of inflation, interest rates, NIM, LDR and Covid-19 Pandemic on NPLs of commercial banks in Indonesia during 2017-2022. The panel data regression method is employed in this research with the research sample consisting of 4 state-owned commercial banks. The results of the study stated that inflation, interest rates and NIM had a significant negative effect on NPL, while LDR and the Covid-19 Pandemic had a significant positive effect on NPL.